Health behaviors of people with multiple sclerosis and its associations with MS related outcomes: a German clinical cohort - Goldin, Katharina; Riemann-Lorenz, Karin; Daubmann, Anne; Pöttgen, Jana; Krause, Nicole; Schröder, Helmut; Heesen, Christoph (Frontiers in Neurology, 2023)
Background Health behaviors in persons with multiple sclerosis (pwMS) have been associated with MS-related disease outcomes. Objective The aim of the study was to gain knowledge about current patient health behaviors in a convenience sample representative for pwMS presenting to a large university-based outpatient clinic and to investigate associations between modifiable risk factors with physical impairment, quality of life (QoL) and cardiovascular comorbidities. Methods A questionnaire was administered at the MS Outpatient Clinic of the University Medical Center Hamburg Eppendorf asking for health behaviors regarding dietary habits assessed with the German adaptation of the validated Spanish short Diet Quality Screener (sDQS), level of physical activity assessed with the Godin Leisure Time Questionnaire (GLTEQ) and tobacco smoking. Participants were asked to report cardiovascular comorbidities using items from the Self-Report Comorbidity Questionnaire for Multiple Sclerosis. Additionally, cardiovascular risk factors like blood pressure, height and weight (to calculate BMI) and waist circumference were measured. MS specific clinical data, e.g., disease course, duration, disability and MS-specific QoL were collected from the clinical database. Descriptive analyses were performed and multivariate regression analyses for complete cases were carried out for each of the three outcome variables including all mentioned modifiable risk factors (dietary behavior, smoking, physical activity and BMI) as independent variables. Results In this sample of 399 pwMS the mean age was 42 years (SD 12.8) with a mean disease duration since diagnosis of 7.4 years (SD 8.4) and a mean EDSS of 2.8 (SD 1.9). 24% were current smokers, 44% were insufficiently physically active and 54% did not follow a healthy dietary pattern. 49% of this relatively young clinical population was overweight and 27% reported one or more cardiovascular comorbidities. Most modifiable risk factors showed no convincing associations with MS-related disease outcomes in the multiple regression analyses. Conclusion This clinical cohort of pwMS shows a high prevalence of critical health behaviors and comorbidities and emphasizes the need for monitoring, education and assistance for behavior change in this population.